Which skills and factors better predict winning and losing in high-level men's volleyball? - Pena, J.; Rodriguez-Guerra, J.; Busca, B.; Serra, N. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to determine which skills and factors better predicted the outcomes of regular season volleyball matches in the Spanish "Superliga" and were significant for obtaining positive results in the game. The study sample consisted of 125 matches played during the 2010-11 Spanish men's first division volleyball championship. Matches were played by 12 teams composed of 148 players from 17 different nations from October 2010 to March 2011. The variables analyzed were the result of the game, team category, home/away court factors, points obtained in the break point phase, number of service errors, number of service aces, number of reception errors, percentage of positive receptions, percentage of perfect receptions, reception efficiency, number of attack errors, number of blocked attacks, attack points, percentage of attack points, attack efficiency, and number of blocks performed by both teams participating in the match. The results showed that the variables of team category, points obtained in the break point phase, number of reception errors, and number of blocked attacks by the opponent were significant predictors of winning or losing the matches. Odds ratios indicated that the odds of winning a volleyball match were 6.7 times greater for the teams belonging to higher rankings and that every additional point in Complex II increased the odds of winning a match by 1.5 times. Every reception and blocked ball error decreased the possibility of winning by 0.6 and 0.7 times, respectively.